The constitutional interpretation of the Federal Supreme Court and its impact on the federal system in Iraq - Comparative analytical study - Mahmood, Abdulfattah Abdulrazaq; Ameen, Bewar Abdulraheem Mohammad (Journal of Legal and Political Studies, 2020)
This research, entitled "The Constitutional Interpretation of the Federal Supreme Court and its Impact on the Federal System in Iraq - A Comparative Analytical Study", deals with the interpretations of the Federal Supreme Court regarding the Constitutional regulation of the federal system in Iraq and the impact of its interpretive decisions on the characteristics and principles of the federal system.and the role of the court in protection of the (idea of federalism)adopted during the drafting of the Iraqi constitution in 2005. All this through the study of the interpretative applications of the Federal Supreme Court of the constitutional texts governing the federal system in Iraq, Whether these applications fall within their direct interpretation when exercising their original competence in interpreting the provisions of the Constitution, or fall within its indirect interpretation when exercising its other competences in adjudicating cases and appeals before it.
Keywords: Constitutional Interpretation; Federal System in Iraq; Supreme Court; federal system; interpretative applications